Innervation Patterns of Sea Otter (Enhydra lutris) Mystacial Follicle-Sinus Complexes - Christopher Douglas Marshall; Christopher Douglas Marshall; Kelly eRozas; Brian eKot; Verena eGill (Frontiers Media S.A., 2014)
Sea otters (Enhydra lutris) are the most recent group of mammals to return to the sea, and may exemplify divergent somatosensory tactile systems among mammals. Therefore, we quantified the mystacial vibrissal array of sea otters and histologically processed follicle-sinus complexes (F-SCs) to test the hypotheses that the number of myelinated axons per F-SC is greater than that found for terrestrial mammalian vibrissae and that their organization and microstructure converge with those of pinniped vibrissae. A mean of 120.5 vibrissae were arranged rostrally on a broad, blunt muzzle in 7-8 rows and 9-13 columns. The F-SCs of sea otters are tripartite in their organization and similar in microstructure to pinnipeds rather than terrestrial species. Each F-SC was innervated by a mean 1339±408.3 axons. Innervation to the entire mystacial vibrissal array was estimated at 161,313 axons. Our data support the hypothesis that the disproportionate expansion of the coronal gyrus in somatosensory cortex of sea otters is related to the high innervation investment of the mystacial vibrissal array, and that quantifying innervation investment is a good proxy for tactile sensitivity. We predict that the tactile performance of sea otter mystacial vibrissae is comparable to that of harbor seals, sea lions and walruses¬.